2015
DOI: 10.1098/rspb.2015.1167
|View full text |Cite
|
Sign up to set email alerts
|

Early and adult social environments have independent effects on individual fitness in a social vertebrate

Abstract: Evidence that the social environment at critical stages of life-history shapes individual trajectories is accumulating. Previous studies have identified either current or delayed effects of social environments on fitness components, but no study has yet analysed fitness consequences of social environments at different life stages simultaneously. To fill the gap, we use an extensive dataset collected during a 24-year intensive monitoring of a population of Alpine marmots (Marmota marmota), a long-lived social r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Between-individual differences in phenotypic attributes such as age (Caughley 1966, Emlen 1970, sex (Short and Balaban 1994), body mass (Sauer and Slade 1987), or personality (Dingemanse and Dochtermann 2013), in genotype (Coulson et al 2011), in habitat use or habitat selection such as home range size or quality (Mcloughlin et al 2007), or in prey selection (Estes et al 2003) have all been reported to affect most life history traits. More recently, both current and early-life environmental conditions encountered by individuals throughout their lives have been shown to generate individual differences in life history traits (Douhard et al 2014, Berger et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Between-individual differences in phenotypic attributes such as age (Caughley 1966, Emlen 1970, sex (Short and Balaban 1994), body mass (Sauer and Slade 1987), or personality (Dingemanse and Dochtermann 2013), in genotype (Coulson et al 2011), in habitat use or habitat selection such as home range size or quality (Mcloughlin et al 2007), or in prey selection (Estes et al 2003) have all been reported to affect most life history traits. More recently, both current and early-life environmental conditions encountered by individuals throughout their lives have been shown to generate individual differences in life history traits (Douhard et al 2014, Berger et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…However, such multivariate analysis is essential for a comprehensive understanding of dispersal and its determinants in family-living species. Previous studies on the effects of kin structure on dispersal have rarely addressed these questions against predictions derived from the effects of kin on other life-history traits, although at least in some species, the effects of kin on traits such as breeding probability and reproductive success can be sex-specific (Nitsch et al, 2013;Scandolara et al, 2014a) or vary across different life-history stages (Sparkman et al, 2011;Nitsch et al, 2013;Berger et al, 2015). Therefore, it is likely that dispersal decisions are most fruitfully examined with an integrative approach that considers effects on all such traits simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…, Takahashi ) and reproductive success (Berger et al . ). However, the source of this variation may also be genetic, as high density sites on breeding colonies are frequently occupied by aggressive, dominant males (Boness et al .…”
Section: Model Output From the Gamm Analyzing Aggression Frequencies mentioning
confidence: 97%
“…There has been a long history of studies investigating the impacts of early social environment on an infant's subsequent behavior in a wide range of animal species, from ants to nonhuman primates (reviewed in Scott 1962). The social environment in which an individual is raised has been shown to exert lifelong effects on adult behavior (Crawley et al 1975, Takahashi 1986) and reproductive success (Berger et al 2015). However, the source of this variation may also be genetic, as high density sites on breeding colonies are frequently occupied by aggressive, dominant males (Boness et al 1982) and females (Pomeroy et al 2000).…”
mentioning
confidence: 99%